Pengaruh Hasil Pemahaman Dan Kepercayaan Terhadap Minat Siswa Menjadi Nasabah Bank Syariah - Bintang fajar nuryanto; Sulthan Fawwaz Muhamad; Ghina Nurfatimah Maharani; Wahyu Hidayat; Zaini Ibrahim (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to analyze and understand the impact of students' comprehension of the profit-sharing system and their level of trust on their interest in becoming customers of Islamic banks. This is important because Islamic banks greatly rely on the trust of students to expand their customer base. The research employs a quantitative analysis method.The results indicate that students' understanding of the profit-sharing system and their level of trust have a positive and significant effect on The students' interest in becoming customers of Islamic banks increases with their better understanding of the profit-sharing concept and stronger trust in Islamic banks. In essence, the more students comprehend profit-sharing and trust Islamic banks, the more inclined they are to become customers.The discussion suggests that to increase the number of customers among students, Islamic banks need to focus on educating them about the profit-sharing system they use, as well as building and maintaining the trust of the students. Initiatives such as outreach programs, seminars, and operational transparency can help enhance this